The roles of specific glycosylases in determining the mutagenic consequences of clustered DNA base damage. - Shikazono, N; Pearson, C; O'Neill, P; Thacker, J (2006)
The potential for genetic change arising from specific single types of DNA lesion has been thoroughly explored, but much less is known about the mutagenic effects of DNA lesions present in clustered damage sites. Localized clustering of damage is a hallmark of certain DNA-damaging agents, particularly ionizing radiation. We have investigated the potential of a non-mutagenic DNA base lesion, 5,6-dihydrothymine (DHT), to influence the mutagenicity of 8-oxo-7,8-dihydroguanine (8-oxoG) when the two lesions are closely opposed. Using a bacterial plasmid-based assay we present the first report of a significantly higher mutation frequency for the clustered DHT and 8-oxoG lesions than for single 8-oxoG in wild-type and in glycosylase-deficient strains. We propose that endonuclease III has an important role in the initial stages of processing DHT/8-oxoG clusters, removing DHT to give an intermediate with an abasic site or single-strand break opposing 8-oxoG. We suggest that this mutagenic intermediate is common to several different combinations of base lesions forming clustered DNA damage sites. The MutY glycosylase, acting post-replication, is most important for reducing mutation formation. Recovered plasmids commonly gave rise to both wild-type and mutant progeny, suggesting that there is differential replication of the two DNA strands carrying specific forms of base damage.